Analisis Perbandingan Return On Assets (Roa) Untuk Mengukur Kinerja Perusahaan Dengan Metode Anova (Studi pada Perusahaan Sub Sektor Makanan dan Minuman: PT Indofood Sukses Makmur Tbk dan PT Mayora Indah Tbk Periode 2021–2025) - Adinda Asri Delima; Gita Rohalia; Pretty Annabel Lusiana; Rafly Al-choiri; Yulia Rahmawati; Sunita Dasman (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the difference in Return on Assets (ROA) between PT Indofood Sukses Makmur Tbk (INDF) and PT Mayora Indah Tbk (MYOR) in the 2021–2025 period. The study uses a comparative quantitative approach with secondary data in the form of annual financial statements published through the Indonesia Stock Exchange. The analysis techniques used included descriptive statistics, Shapiro-Wilk normality test, Levene's Test variance homogeneity test, and One-Way ANOVA. The results of the normality test showed that the ROA data of the two companies was normally distributed (Sig. INDF = 0.694; MYOR = 0.871). The variance homogeneity test was also met (Sig. = 0.125). The results of the One-Way ANOVA test showed a significance value of 0.027 (< 0.05), which means that there is a statistically significant difference in average ROA between the two companies. The average ROA of PT Mayora Indah Tbk (9.620%) is higher than that of PT Indofood Sukses Makmur Tbk (6.226%).